Surface modification of biomaterials based on cocoa shell with improved nitrate and Cr(vi) removal. Issue 34 (27th May 2020) - Fotsing, P. Nkuigue; Woumfo, E. Djoufac; Mezghich, S.; Mignot, M.; Mofaddel, N.; Le Derf, F.; Vieillard, J.
Abstract : The present work addresses the development of simple, low-cost and eco-friendly cocoa-shell-based materials for efficient removal of heavy metal hexavalent chromium (Cr(vi )), and toxic nitrate (NO3 − ) from aqueous solution. Abstract : The present work addresses the development of simple, low-cost and eco-friendly cocoa-shell-based materials for efficient removal of heavy metal hexavalent chromium (Cr(vi )), and toxic nitrate (NO3 − ) from aqueous solution. A conventional treatment process was used to purify cocoa shell (CS) into an adsorbent, followed by chemical grafting of dendrimers to promote its surface properties for nitrate and Cr(vi ) removal. The morphology, surface charge, structure and stability of the new adsorbent were investigated by scanning electron microscopy, Fourier transform infrared and UV-visible spectroscopies, zeta potential, X-ray photoelectron spectrometry, and differential scanning calorimetry. The successful chemical grafting of the dendrimer (polyethyleneimine, PEI) onto purified CS was confirmed. CS-T-PEI-P proved to be a very efficient candidate for the removal of nitrate and chromium(vi ). Removal of the two pollutants at different initial concentrations and pH values was studied and discussed. Sorption of chromium and nitrate was found to obey 2 nd -order kinetics and a Freundlich-type isotherm, affording an uptake adsorption of 16.92 mg g −1 for NO3 − and 24.78 mg g −1 for Cr(vi ). These results open promising prospects for its potential applications as a low cost catalyst in wastewater treatment.